MODEL KAIDAH KEPUTUSAN UNTUK MENGETAHUI ELEMEN DESAIN KEMASAN PEMBENTUK PERSEPSI KONSUMEN - Azrifirwan, Taufik Djatna, Syamsul Maarif, Mirwan Ushada, Endang Warsiki (Jurnal Teknologi Industri Pertanian, 2017)
The packaging design elements that have appeal and take into account consumers' Kansei are crucial in introducing new products and influencing purchasing decisions. Integration of packaging design elements to produce a certain character has a combination and complexity, but can produce unequal perception. To reduce the emergence of perceptual ambiguity, then in the design process requires a measurable and standard model. The purpose of research were to design the attributes and sub elements and to make the decision rules so that the knowledge obtained underlying consumer expression. This research used a combination of Business Process Model Notation method to explain activity and data flow, Relief and Principle Component Analysis method to select design attributes and packaging selection, and Bayes Rough Set method to get the combination of decision rule. The results obtained represented the design elements and packaging samples such as size, colour, letter writing, and packaging bottle grouping as a means of reducing the number of samples. The Kansei expression of seriously was explained by a combination of text writing products that were not legibility, small font size, single color on the text, the dominant color of brown labels, black, green and no illustration of the image. The Kansei expression of eye cathing was explained by the combination of the design attributes of the sharpness of the colour, the text of the product, the text size of the product, the product text colour and the dominant colour, and the water illustration. The ergonomic aspect of bottled beverage design was that if it has a combination of high-element proportional bottles, it has a curved, low bottle cap, and a small bottle bottom diameter.Keywords: bayes rough set, design element,  decision rule, kansei